The Selection System for the Suitable Representatives in Thai Society - serirangsan, thirapat (King Prajadhipok’s Institute Journal, 2020)
The selection system of the representatives in Thai Society is determination how to choose members of the House of Representatives and Senators, it is unavoidable to involve with the process or source of administrative section. On the other hand, the solution of the research may not only related to assemblymen and senators, but also executive section. The result of this research showed that there are 5 conclusions drawn from inquiring the samples as follows: (1) The selection of a Prime Minister through set up elections directly to people, (2) Political party which has the most voting of proportional representatives must have the authorities to form a government and the chief will be the Prime Minister who separate power between legislative power and executive, (3) The election of representatives still managed by mixed pattern from constituent system to proportion. Moreover, the numbers of both kinds of representatives must be the same and the vote of proportional representation would define the members along with the election in Germany. (4) Being the same tradition of selection and component representatives and senators under the Constitution of the Kingdom of Thailand B.E. 2540 and B.E. 2550, (5) Focus on considering the high qualification of representatives, building strong moral system and the system of checks and balances regardless of the selection and component of political office holders. Every process can be obtained by the new Constitution of Thailand must be rewritten and listen to the needs or majority opinions of people as resolution. Also, process (4) and (5) should be added to other processes (process 1, 2 or 3) for seriousness and effectiveness of concrete controlling, and this would help the qualitative democracy more or less successfully.